Artificial impedance approach to the collision avoidance of robots with obstacles. - Jassemi-Zargani, Rahim. (University of Ottawa (Canada), 1990)
Among the desired features for robot manipulation in future applications are autonomous trajectory generation and automatic collision avoidance. In this thesis, the Impedance control method is used for the trajectory generation of a revolute manipulator in free motion, and for obstacle avoidance. In the Impedance control method, a desired mechanical impedance between the robot end-effector and the target is generated by modulating the force or torque output of the robot actuators. An approach using Impedance control, in conjunction with 'Coastal and Surface Navigation' concept, is developed for generating trajectories in non-convex spaces utilizing proximity-sensor data.
Keywords: Engineering, Mechanical.